(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the accuracy of digital radiographic templating of total hip arthroplasty implants when compared with actual intra operative sizes used. Methods: This cross sectional study was conducted in Orthopedics and Spine Surgery Department Hayatabad Medical Complex Peshawar from 23rd January 2020 to 23rd January 2021.Preoperative templating was done on anteroposterior pelvic radiographs followed by cemented total hip arthroplasty(THA). The templating measurements were compared with actual sizes of implants used based upon actual intra operative anatomical measurements. Results: In this study 60 patients were included. Male patients were 38(63.3%) and females were 22(36.7%). The mean age was 61.9±3.40 years. The preoperative templating perfectly matched with the intraoperative stem sizes actually used in 42(70 %). Plus minus one size error variation was noted in 13( 21.7 % ) patients while in 5(8.3%) patients there was gross variation error in size. The preoperative templating perfectly matched with the intraoperative cup sizes used in 42(70%).Plus minus one error size variation was documented in 10(16.7%) while gross error in variation in size was noted in 8(13.3%) patients. Conclusion: The preoperative radiographic templating of stem and cup size perfectly matched with intraoperative implants used in total hip arthroplasty in majority of our patients. We recommend pre operative templating a mandatory step in all patients with total hip arthroplasty.